1999
DOI: 10.1097/00006123-199910000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Odontoid Fractures with Single-screw Anterior Fixation

Abstract: Single-screw anterior odontoid fixation was associated with a relatively low complication rate and a high fusion rate in this study. We think that this should be the preferred treatment method for acute Type II odontoid fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 31 publications
1
92
0
9
Order By: Relevance
“…Julien et al [14] reviewed a mean overall union rate of 85.5% with posterior instrumented fusion of C1-2, while the fusion rates after AOSF were reported with 95, 90% for Type II and 100% for Type III. The results were echoed in several other studies with fusion rates ranging 84-96% [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Julien et al [14] reviewed a mean overall union rate of 85.5% with posterior instrumented fusion of C1-2, while the fusion rates after AOSF were reported with 95, 90% for Type II and 100% for Type III. The results were echoed in several other studies with fusion rates ranging 84-96% [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 71%
“…First described by Bohler [13], several studies also reported on technical details, surgical outcomes and complications [2,6,[14][15][16][17][18][19][20][21][22][23][24][25]. AOSF allows osteosynthesis of reduced OF through a non-traumatic standardized surgical approach if compared to the posterior approach [26] and can preserve atlantoaxial motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But 35% judged their outcome as moderate or poor and 20% assumed that they would need additional treatment for their neck condition in the future. In contrast, in literature the results of various treatment modalities for C2-fractures, particularly for odontoid fractures, were frequently recognized as 'good' if not 'excellent' [25,62,72]. In the past, detailed data have been sparse commonly not exceeding cross-sectional assessments and despite the prevailing opinion that overall outcome was favourable, long-term analysis identified persisting symptoms of pain and stiffness in a meaningful number of patients [1,11,57,76].…”
Section: Clinical Outcomementioning
confidence: 99%
“…The lack of a comprehensive treatment-oriented classification of C2-fractures, that guides when to operate and when to select conservative treatment, reflects the fact that there exists no ideal solution for the clinical problem, yet [56]. In contrast, there is a large body of literature concerning techniques, indications and union rates in C2-fractures [72], but data regarding the most important outcome measure, the functional and clinical outcome, are scant [24,68]. Currently, in addition to nonsurgical treatment including semirigid collars or the Halo-thoracic-vest (HTV), contemporary surgical techniques for the treatment of C2-fractures include anterior odontoid screw fixation (AOSF) [2,62], posterior and anterior transarticular screw fixation C1-2 [51], C1-lateral mass and C2-Isthmus/lamina fixation [32] and plated anterior discectomy and fusion for the unstable Hangman's fracture (Hmfx) [46,83].…”
Section: Introductionmentioning
confidence: 99%